Класифікація даних обліку електричної енергії - Коцар, О. В. (Видавництво Львівської політехніки, 2018)
Управління даними обліку електроенергії передбачає послідовне перетворення результатів вимірювань на дані комерційного обліку, зокрема агреговані, їхню верифікацію та валідацію у встановленому порядку з метою інформаційного забезпечення розрахунків за електричну енергію та завдань управління попитом. Комплексне забезпечення точності, повноти, цілісності, достовірності та актуальності даних комерційного обліку потребує системного підходу, який ґрунтується на класифікації даних обліку, зокрема, за належністю, походженням, станом оброблення, ступенем автоматизації тощо. Досліджено порядок та стадії формування даних обліку електроенергії, визначено і систематизовано класифікаційні ознаки та розроблено систему класифікації даних обліку електричної енергії. Результати досліджень застосовано під час формування ознак якості (достовірності) даних обліку, а також розроблення (вдосконалення) методів верифікації та валідації даних обліку, зокрема в умовах лібералізації ринку електричної енергії України.

Electricity metering data management understands the consistent conversion of measurement results into commercial metering data, in particular, aggregated, verified and validated in accordance with the established procedure for the purpose of providing information support for electricity payment and demand side management tasks. Comprehensive assurance of the precision, completeness, integrity, authenticity and relevance of commercial metering data requires a system approach based on the metering data classification, in particular, the identification of classification characteristics and the development of a structured classification system for the metering data aiming formation of attributes of the metering data reliability as well as developing new methods of metering data verification and validation at the different levels of distributed Smart Metering System. In practice, it is worth justifying the expediency of classifying metering data by the one or another of the characteristics for solving specific tasks. In particular, the basis for the verification of commercial metering data could be put the possibility of determining them through the application of formalized and approved in an established manner processing algorithms and procedures. Proposed metering data classification allows assess the degree of trust in the metering data and on the basis of authenticity assign this data a status «reliable», «unreliable» or to allocate separate warnings concerning the reliability of the data. Classification of data by the status of in-house verification may be useful, for example, for documenting the results of metering data phased preparation for further application, in particular, for calculating electricity costs. Results of the research were applied during the formation of the attributes of the metering data quality (authenticity), as well as the metering data verification and validation methods development (improvement) in electricity market of Ukraine.
Classification of electricityaccount data
Keywords: АСКОЕ; дані обліку; достовірність; класифікація; ринок електричної енергії; AMI; smart meter; smart metering system; metering data; authenticity; classification; electricity market